Type 1 diabetes in children born after assisted reproductive technology: a register-based national cohort study. Issue 1 (24th January 2020) - Norrman, E; Petzold, M; Clausen, T D; Henningsen, A-K; Opdahl, S; Pinborg, A; Rosengren, A; Bergh, C; Wennerholm, U-B
References: STUDY QUESTION: Do children born after assisted reproductive technology (ART) have an increased risk of developing type 1 diabetes? SUMMARY ANSWER: Children born after ART were found to have an increased risk of type 1 diabetes in the unadjusted analysis, while after adjustment this association was only significant in children born after frozen embryo transfer. WHAT IS KNOWN ALREADY?: Some studies raise concerns as to whether fertility treatments may influence long-term morbidity in children born after ART. Elevated blood pressure and altered glucose metabolism have been found after ART in a few studies. STUDY DESIGN, SIZE, DURATION: A register-based national cohort study that included all children born in Sweden between 1985 and 2015—in total, 3 138 540 children—was carried out. PARTICIPANTS/MATERIAL, SETTING, METHODS: The study was population-based and all live-born singleton children born after ART ( n  = 47 938) or spontaneous conception (SC) ( n  = 3 090 602) were included. The ART cohort comprised 36 727 children born after fresh embryo transfer and 11 211 children born after frozen embryo transfer. Several national registries were used together with data from Statistics Sweden. MAIN RESULTS AND THE ROLE OF CHANCE: In total, 202 children born after ART and 17 916 children born after SC developed type 1 diabetes, corresponding to 43.4 and 35.5 per 100 000 person-years at risk (hazard ratio [HR] 1.23; 95% confidence interval [CI], 1.07 to 1.42). Mean follow-up was 9.7 (SD 6.4) years for ART children and 16.3 (SD 9.2) years for SC children. After adjustment for calendar year of birth, HR for type 1 diabetes was 1.13; 95% CI, 0.98–1.30. After further adjustment for sex, maternal age, country of birth, educational level, smoking and parental diabetes, HR was 1.07; 95% CI, 0.93–1.23. In subgroup analyses, an association was found between frozen embryo transfer and type 1 diabetes (adjusted HR 1.52; 95% CI, 1.08–2.14 and 1.41; 95% CI, 1.05–1.89 for frozen versus fresh and frozen versus SC, respectively). When comparing intracytoplasmic sperm injection to in vitro fertilization, no difference was found (adjusted HR 1.08; 95% CI, 0.77–1.51). LIMITATIONS, REASONS FOR CAUTION: Limitations were the missing data and residual confounding caused by unknown confounders. Furthermore, the control group consisted of all children not conceived by ART and not non-ART children from subfertile mothers. The study was also performed in only singletons and not in the total ART population. WIDER IMPLICATIONS OF THE FINDINGS: Type 1 diabetes is a serious disease, affecting human life in several ways, including risk of serious complications, reduced life span and a life-long treatment. Our results are generally reassuring, showing no increase in diabetes in ART children compared to children born after SC after adjustment for relevant confounders. The observation of an association between children born after frozen embryo transfer and type 1 diabetes, although based on subgroup analyses with a limited number of children and modest in size, is however a reason for concern. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by Nordforsk 71450, the Swedish state under the agreement between the Swedish government and the county councils, the ALF-agreement 70940, and the Hjalmar Svensson Foundation. The authors have no competing interests. TRIAL REGISTRATION NUMBER: ISRCTN 11780826.